Alternative Shakespeares - Drakakis, John; Hawkes, Terence (New accents (Methuen & Co.), 1985)
Introducing new debates and new theorists, this collection provides a broad cross-section of contemporary Shakespearen studies, including psychoanalysis, sexual and gender politics, race and new historicism. Shakespeare for the 21st c.